1987
DOI: 10.1098/rsta.1987.0081
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear wave motion governed by the modified Burgers equation

Abstract: The modified Burgers equation (MBE) ∂ V ∂ X + V 2 ∂ V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…For parts 3 (left curve), 4 (tail shock), 5 (right curve) and 6 (head shock) analytic lowest approximation solutions are given by Lee-Bapty and Crighton [10]. For part 7 (right tail) an analytic solution is still not yet found.…”
Section: Propagating N-waves In a Cubically Nonlinear Mediummentioning
confidence: 99%
“…For parts 3 (left curve), 4 (tail shock), 5 (right curve) and 6 (head shock) analytic lowest approximation solutions are given by Lee-Bapty and Crighton [10]. For part 7 (right tail) an analytic solution is still not yet found.…”
Section: Propagating N-waves In a Cubically Nonlinear Mediummentioning
confidence: 99%
“…In some special cases it is reducible to cubic Burgers-type equation studied in Ref. [9] for plane waves and in Ref. [5,10] for spatially-limited beams.…”
Section: Cubic Resonatormentioning
confidence: 99%
“…For example, the shock formation time is on the order of the inverse square of the wave amplitude when the nonlinearity is cubic as compared to inversely proportional when the nonlinearity is quadratic. A more complete discussion of these nonclassical dynamics may be found in the thesis by Lee-Bapty ( 1981 ) or the article by Lee-Bapty and Crighton (1987).…”
Section: Introductionmentioning
confidence: 99%
“…A more detailed study of the distortion of shear waves is presented by Lee-Bapty ( 1981 ) who demonstrated that the basic wave evolution is fundamentally different than that exhibited by longitudinal waves. The nonlinearity of relatively weak longitudinal waves is quadratic leading to the generation of second harmonics when wave trains are considered, whereas the nonlinearity of shear waves in an initially unstrained matehal is seen to be cubic.…”
Section: Introductionmentioning
confidence: 99%